An IoT Solution: A Fitness Trainer - Hladkyi, Yaroslav; Gladka, Myroslava; Kostikov, Mykola; Lisnevskyi, Rostyslav (My University, 2021)
An IoT system of motion detection and control for fitness exercises can be urgent for people who do sports at home. Using such a system as a mobile application allows the user to get the assessment of technique when doing exercises demonstrating them in front of the smartphone camera, as well as recommendations which may help improve doing exercises. As a result, the efficiency of exercises will be increased. These functions are implemented via a neural network able to recognize images. Besides, users will see their progress and information on exercises made with flaws, which will help to fix the execution technique. The IoT system configures business rules and scenarios, necessary artefacts for users, the exercises they perform, errors and deviations that are committed while doing the exercises, as well as analyzing video files. The IoT solution is built using a neural network that is capable of recognizing the user's body posture during the exercise using a video file captured on the camera of their own smartphone. With the help of mathematical calculations, artificial intelligence will return the result of the video file analysis, where the user will be able to see their flaws while doing a certain task, and get recommendations. A special factor in pattern recognition is the individual initial anthropometric data of each user, which must be taken into account in the analysis. The use of IoT system of monitoring and control over the performance of fitness exercises will positively affect the trend of a healthy lifestyle in today's world without the involvement of personal fitness trainers.

Для людей, які займаються спортом вдома, може бути актуальною система IoT для виявлення та контролю руху для фітнес-вправ. Використання такої системи як мобільного додатку дозволяє користувачеві отримати оцінку техніки виконання вправ, демонструючи їх перед камерою смартфона, а також рекомендації, які можуть допомогти покращити виконання вправ. В результаті підвищиться ефективність вправ. Ці функції реалізуються через нейронну мережу, здатну розпізнавати зображення. Крім того, користувачі бачитимуть свій прогрес і інформацію про вправи, зроблені з недоліками, що допоможе виправити техніку виконання. Система IoT налаштовує бізнес-правила та сценарії, необхідні артефакти для користувачів, вправи, які вони виконують, помилки та відхилення, які допускаються під час виконання вправ, а також аналізує відеофайли. Рішення IoT створено за допомогою нейронної мережі, яка здатна розпізнавати позу тіла користувача під час вправи за допомогою відеофайлу, знятого на камеру його власного смартфона. За допомогою математичних розрахунків штучний інтелект поверне результат аналізу відеофайлу, де користувач зможе побачити свої недоліки під час виконання певного завдання та отримати рекомендації. Особливим фактором розпізнавання образів є індивідуальні вихідні антропометричні дані кожного користувача, які необхідно враховувати при аналізі. Використання IoT системи моніторингу та контролю за виконанням фітнес-вправ позитивно вплине на тренд здорового способу життя в сучасному світі без залучення персональних фітнес-тренерів.
Keywords: IoT; system; neural network; image recognition; fitness; training; technique; mobile application; кафедра інформаційних технологій, штучного інтелекту і кібербезпеки